Crosstalk among long non-coding RNA, tumor-associated macrophages and small extracellular vesicles in tumorigenesis and dissemination - Zhang, Li-jie; Chen, Feng; Liang, Xiao-ru; Ponnusamy, Murugavel; Qin, Hao; Lin, Zhi-juan (Frontiers in Oncology, 2022)
Abstract: Long noncoding RNAs (lncRNAs), which lack protein-coding ability, can regulate cancer cell growth, proliferation, invasion, and metastasis. Tumor-associated macrophages (TAMs) are key components of the tumor microenvironment that have a significant impact on cancer progression. Small extracellular vesicles (sEV) are crucial mediators of intercellular communications. Cancer cell and macrophage-derived sEV can carry lncRNAs that influence the onset and progression of cancer. Dysregulation of lncRNAs, TAMs, and sEV is widely observed in tumors which makes them valuable targets for cancer immunotherapy. In this review, we summarize current updates on the interactions among sEV, lncRNAs, and TAMs in tumors and provide new perspectives on cancer diagnosis and treatment.